Randomised controlled trial of magnetic bracelets for relieving pain in osteoarthritis of the hip and knee. Issue 7480 (16th December 2004) - Harlow, Tim; Greaves, Colin; White, Adrian; Brown, Liz; Hart, Anna; Ernst, Edzard
Abstract: Objective To determine the effectiveness of commercially available magnetic bracelets for pain control in osteoarthritis of the hip and knee. Design Randomised, placebo controlled trial with three parallel groups. Setting Five rural general practices. Participants 194 men and women aged 45-80 years with osteoarthritis of the hip or knee. Intervention Wearing a standard strength static bipolar magnetic bracelet, a weak magnetic bracelet, or a non-magnetic (dummy) bracelet for 12 weeks. Main outcome measures Change in the Western Ontario and McMaster Universities osteoarthritis lower limb pain scale (WOMAC A) after 12 weeks, with the primary comparison between the standard and dummy groups. Secondary outcomes included changes in WOMAC B and C scales and a visual analogue scale for pain. Results Mean pain scores were reduced more in the standard magnet group than in the dummy group (mean difference 1.3 points, 95% confidence interval 0.05 to 2.55). Self reported blinding status did not affect the results. The scores for secondary outcome measures were consistent with the WOMAC A scores. Conclusion Pain from osteoarthritis of the hip and knee decreases when wearing magnetic bracelets. It is uncertain whether this response is due to specific or non-specific (placebo) effects.